2021
DOI: 10.3390/agronomy11112161
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen Fertilization on Yield and Macronutrient Concentrations in Three Cultivars of Jerusalem Artichoke (Helianthus tuberosus L.)

Abstract: In many countries, Jerusalem artichoke (JA) is a source of biomass for renewable energy production and alternative biofuel feedstock, and it is used for feed and food production. The species also has medicinal properties, and it is used in soil reclamation. The aim of this study was to evaluate the effect of N fertilization on the yield and macronutrient concentrations in JA tubers. The effect of N fertilization (control plot, unfertilized, 80 and 120 kg ha−1) on aerial biomass yield, tuber yield, and the mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The maximum plant height was recorded at an optimum N fertilizer concentration, while the shortest height was observed in the control group (Figure 1). The optimum level of nitrogen stimulates the production of cytokines, which affects the flexibility of cell walls, the proliferation of meristematic cells, and overall cell growth [37]. However, Kukal [38] was of the view that the high temperature of the air and soil causes the alteration in water transport in the plant, which ultimately reduces stomatal conductance and causes low productivity and yield.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum plant height was recorded at an optimum N fertilizer concentration, while the shortest height was observed in the control group (Figure 1). The optimum level of nitrogen stimulates the production of cytokines, which affects the flexibility of cell walls, the proliferation of meristematic cells, and overall cell growth [37]. However, Kukal [38] was of the view that the high temperature of the air and soil causes the alteration in water transport in the plant, which ultimately reduces stomatal conductance and causes low productivity and yield.…”
Section: Discussionmentioning
confidence: 99%
“…The highest yields of JA aerial biomass (up to 40 Mg DM ha −1 y −1 ) are noted in Western and Southern Europe (Germany, Italy, Spain, Austria) [43,79,80,84] and in Eastern and Central Asia (China) [36,65,81]. The DMY of JA tubers accounts for 27-45% [81,84,86,90] to 72% [41,91] of the total DMY of aerial biomass and tubers. Sawicka [44] found that tuber yields are significantly affected by soil and climatic conditions.…”
Section: Biomass Yieldmentioning
confidence: 99%